Reply to Comment on Spin-selective reactions of radical pairs act as quantum measurements - Jones, J; Maeda, K; Steiner, U; Hore, P (2011)
In his Comment on a recent paper by two of us Kominis claims that the recently proposed quantum measurement model for spin-selective reactions of radical pairs leads to ambiguous predictions in a simple case. Here we show that this claim is based on a confusion between the unreacted and unrecombined portions of the radical pairs, and to an incorrect interpretation of the improper density matrices used in both our model and the conventional Haberkorn model of such reactions. We further show that if this error is corrected then the supposed ambiguity is resolved.